Design So-Unic Sales Accounting Information System At LSM Bombers Corporation Center - Hery Dwi Yulianto; Dinda Syavira Arviandita; S Supriyati (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2012)
LSM Bombers Corporation Center where located at Cikupa RT02/01 No. 106, Ds. Padasuka, Kecamatan Kutawaringin, Kabupaten Bandung is one of home industry company there is move at drink plastic bottle recycle become one kind of handycraft and the result of product they created have value and use for life. Writer doing research at marketing division, which where make of sales report still use Microsoft Office Excel 2007 as counting tool. By that problems writer propose a little "Design Of So-Unic Sales Accounting Information System At LSM Bombers Corporation Center Use PHP and MySQL".